Los controles contables y su incidencia en la contabilidad de la compañía Juvegran Cía. Ltda., ubicada en la parroquia Puná de la provincia del Guayas - Herrera Díaz, Carolina Emérita (2012)
The present thesis entitled Accounting controls and their impact on the company's accounting Juvegran Cía. Ltda. located in the parish Puná province of Guayas, aims to highlight the importance and support that provides a manual of internal accounting control, to develop their business within a proper control environment. That is why I developed this thesis in the company Juvegran Cia. Ltd., the same as it is structured as follows: Chapter 1 deals with the research topic, the problem, its contextualization, critical analysis, prognosis, rationale and both general and specific objectives of the proposal. Chapter 2 discusses the theoretical framework: background research, legal reasoning, fundamental categories, pointing out the assumptions and variables. Chapter 3 discusses the methodology used for the implementation of this thesis research approach, method and level of basic research, population or sample, operationalization of variables and data collection. In Chapter 4 we will analyze and interpret the results of the methodologies discussed in Chapter interior. Finally Chapter 5 details the proposal and implementation of this thesis, with the procedures and details of its implementation for obtaining good results in the company.